Designing a Supply Chain Management Model for Sharia Medical Textile Products Study at PT XYZ - Wijayanto, Hardian (Jurnal Tekstil, 2024)
This research focuses on designing a supply chain management model for Sharia-compliant medical textile products at PT XYZ, in response to the growing demand for halal medical textile products in Indonesia. Sharia medical textiles include products such as masks, medical clothing, and bandages produced in accordance with Islamic law, ensuring the use of halal materials, cleanliness in production processes, as well as fair and transparent business practices. With the increasing number of Sharia hospitals, it is crucial for PT XYZ to consider factors such as religious compliance, safety, security, and product quality throughout the supply chain.This study uses a descriptive-qualitative method, collecting data through interviews, observations, and document studies. The analysis is conducted using dynamic simulation and SWOT analysis, focusing on compliance with Sharia principles, such as halal raw materials and clean production processes. The developed supply chain management model is optimized through procurement, production, and distribution that align with Sharia principles, and it is evaluated through optimistic, realistic, and pessimistic scenarios. The resultsshow that this model has the potential to improve the efficiency and effectiveness of PT XYZ's supply chain while ensuring compliance with halal standards. This research provides a practical framework for integrating Sharia principles into the medical textile supply chain, supporting the development of halal products in Indonesia's healthcare market.